Combined assessment of displacement sensors and motion parameters of the model of light aircraft - Кліпа, А. М. (Problems of Informatization and Control, 2012)
Proposed procedure for evaluation of the combined displacement sensors and parameters of the model of the aircraft with short reiodami on the results of the flight ekspirementa the presence of noise measurement and displacement sensors. Efficiency gains of the proposed procedure tested on benchmark-motion model with short reiodami lehko aircraft DHC-2 «Beaver»